PENGARUH PENDEKATAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR MAHASISWA PENDIDIKAN BIOLOGI SEMESTER VI PADA MATERI KULTUR JARINGAN TANAMAN - Fanny Nella Nanlohy; Verawaty I.Y. Roring; Meity Tanor; Yohanes Bery Mokalu (LPPM Politeknik Saint Paul Sorong, 2023)
This study tries to apply an inquiry approach, which is a constructivist learning method. In this approach, students are given a problem in a particular situation or phenomenon that stimulates them to think critically, analyze and even draw conclusions based on prior knowledge. Through this approach, students are invited to study a problem that must be observed and scrutinized, so that it is hoped that understanding of course concepts in learning activities can increase. In the context of plant tissue culture courses, the learning methods that have been applied so far are less varied, and this seems to have a negative impact on student learning outcomes. Therefore, this study aims to examine the effect of the application of the guided inquiry method on the learning outcomes of semester VI students in that course. It is hoped that with the application of the inquiry method, students will experience an increase in understanding of concepts and skills in plant tissue culture courses. And of course, this increase is expected to have a positive impact on overall learning outcomes. This study used a quasi-quasi experimental design with subjects in the sixth semester of biology students. Data obtained through pretest and post-test, and the hypothesis was tested using the t test. The results of the data analysis show that there is a significant effect of the application of the inquiry method on improving student learning outcomes in tissue culture engineering courses. This can be concluded from the calculated t value which is greater than t table at a significance level of 0.05. Thus, it can be confirmed that the inquiry approach contributes positively to improving student learning outcomes in these courses.